2010
DOI: 10.1213/ane.0b013e3181d31ea6
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor and Insulin-Like Growth Factor Rescue Growth Cones of Sensory Neurites from Collapse After Tetracaine-Induced Injury

Abstract: bFGF and bIGF decreased growth cone collapse after tetracaine-induced injury in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…FGF-2 also interacts with other GFs in lesion regions to promote multiple biological effects. Seki et al found that the application of FGF-2 and IGF in different ratios resulted in different degrees of rescued growth cone collapse in sensory neurons [ 135 ]. In addition, the administration of exogenous FGF-2 benefited interleukin-6 and its related receptor expression in differentiated and proliferating SCs, respectively [ 136 ].…”
Section: The Roles Of Ngf and Fgf-2 In Pnimentioning
confidence: 99%
“…FGF-2 also interacts with other GFs in lesion regions to promote multiple biological effects. Seki et al found that the application of FGF-2 and IGF in different ratios resulted in different degrees of rescued growth cone collapse in sensory neurons [ 135 ]. In addition, the administration of exogenous FGF-2 benefited interleukin-6 and its related receptor expression in differentiated and proliferating SCs, respectively [ 136 ].…”
Section: The Roles Of Ngf and Fgf-2 In Pnimentioning
confidence: 99%
“…During the axonal regeneration, IGF-1 has been shown to play a critical role in SCs by promoting their survival, proliferation, maturation, and differentiation to myelinating phenotypes 33 35 . IGF-1 has been also reported to increase the survival and axonal outgrowth of neurons 36 38 . Our work firstly investigated the target regulation of miR-129 in affecting regenerative microenvironment to further regulate the proliferation and migration of primary SCs, and neurite outgrowth of DRG neurons.…”
Section: Discussionmentioning
confidence: 98%
“…IGF-1 is a basic peptide composed of 70 amino acids with a variety of functions in neuronal cells ( Zheng and Quirion, 2006 ; Croci et al ., 2011 ). IGF-1 plays an important role in promoting axonal growth from DRG neurons ( Bomze et al ., 2001 ; Jones et al ., 2003 ; Seki et al ., 2010 ) and supports to a population of predominantly nociceptive neurons in DRG which may contribute to neuropathic pain ( Craner et al ., 2002 ; Miura et al ., 2011 ). Exogenous administration of IGF-1 after injury is neuroprotective and improves long-term neurological function ( Guan, 2008 ).…”
Section: Discussionmentioning
confidence: 99%